Immunogenicity and safety of single booster dose of KD-414 inactivated COVID-19 vaccine in adults: An open-label, single-center, non-randomized, controlled study in Japan. Issue 1 (31st December 2023) - Terada-Hirashima, Junko; Takamatsu, Yuki; Shimizu, Yosuke; Uemura, Yukari; Takeuchi, Junko S.; Tomita, Noriko; Matsuda, Kouki; Maeda, Kenji; Yamamoto, Shohei; Fukunaga, Ami; Ohmagari, Norio; Mikami, Ayako; et al.
ABSTRACT: Although vaccines for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) disease 2019 (COVID-19) induce effective immune responses, vaccination with booster doses is necessary because of waning immunity. We conducted an open-label, non-randomized, single-arm study in adults in Japan to assess the immunogenicity and safety of a single booster dose of the KD-414 purified whole-SARS-CoV-2-virion inactivated vaccine candidate after vaccination with a primary series of BNT162b2. The primary endpoint was serum neutralizing activity at 7 days after booster injection compared with the primary series of BNT162b2. The SARS-CoV-2-structural protein-binding antibody level and T cell response against SARS-CoV-2-Spike (S) peptides were also examined as secondary endpoints, and safety profile assessments were conducted. Twenty subjects who participated in a previous study declined an injection of KD-414 (non-KD-414 group) and received a booster dose of BNT162b2 instead. The non-KD-414 group was compared to the KD-414 group as a secondary outcome. A single dose of KD-414 induced lower serum neutralizing activity against the wild-type virus within 7 days compared to after the primary series of BNT162b2 but significantly induced anti-SARS-CoV-2-S1-receptor-binding domain-binding immunoglobulin G (IgG) antibodies and SARS-CoV-2-S peptide-specific CD4 + and CD8 + T cell responses. Local or systemic symptoms were significantly lower in the participants who received KD-414 than in those who received BNT162b2 as the third COVID-19 vaccine dose. The present data indicate that a single booster dose of KD-414 induces a substantial immune response in BNT162b2-primed individuals and has a good safety profile, thereby supporting further clinical trials to identify rational targets.